Needs Assessment of ICT Integrated Teaching Ability Development for Primary School Teachers under the Office of the Private Education Committee (Private School) - ดุลยากร, วาเลน; กรณีกิจ, ประกอบ; คล้ายสังข์, จินตวีร์ (Journal of Education Studies, Chulalongkorn University, 2019)
The purpose of this study wasto assesstheneeds required to develop ICT integrated teaching ability for primary school teachers under the Office of the Private Education Committee (Private school). The survey was conducted using questionnaires.The sample was 387 teachers, using a multi-stage sampling technique. The study indicated that mostof the teachers have a number of ICT used hours of less than 6 hours per week (38.5%)and most of them have apercentageof ICT used hours per total teaching hours per week between 21-40% (24.3%). Analyzing the needs for ICTintegrated teaching, the highest PNImodifiedvaluewere the use of ICT in Pre-testing,followedby the use of ICT in Post-testing and the use of ICT in checking students' understanding during classes. Whenanalyzing the needs for ICT integrated teaching abilitydevelopment, the first priority was to have external expertswith ICT integrated experience to guide how to choose ICT in teaching, followed bycollaborativelyworking together with peersto produceICT media and prepare related tools, and a collaborative effort in designing ICT-based classroom to solve student problems.